Fluoride contamination of water: origin, health effects and remediation methods - Mandal, Sujata; Mayadevi, S. (Fluoride, 2011)
Fluorine is the 13th most abundant element in the earth?s crust. It exists in trace amounts in ground water all over the world. Drinking water is the primary source through which fluoride enters the human body, especially in regions where fluoride concentrations in groundwater and/or surface water are high. It is estimated that more than 200 million people worldwide depend on drinking water with fluoride concentration exceeding the present World Health Organization (WHO) guideline (Maximum contaminant level of 1.5 mg/l). Fluoride bearing foodstuffs and fumes from burning of coal also significantly contribute to the daily intake of people in some regions. Prolonged consumption of excess fluoride may lead to different types of fluorosis (dental and skeletal) depending on the level and period of exposure. Presence of fluoride in drinking water above permissible level has been related to increased incidence of fluorosis among the people all over the world including China, India, Australia, Mexico, Argentina, Egypt and Kenya. In India, the problem of excessive fluoride in groundwater was first reported in 1937 in the state of Andhra Pradesh. More than 6 million people all over India are known to be seriously affected by fluorosis and another 62 million are exposed to it. The best choice for combating fluorosis is to have alternative source of water with low fluoride level. In absence of alternative source of water, defluoridation of excess fluoride in water is the only option. Different methods are available for defluoridation of water. But the selection of the appropriate method for achieving a sustainable solution to the fluorosis problem is very important. Defluoridation of drinking water by adsorption is the most simple and effective technology that can work in household as well as community level drinking water treatment. It is also the most widely studied method for defluoridation of water, as the fluoride concentration in groundwater is usually very low (10 mg/l). A wide variety of adsorbents have been explored for this purpose. Synthetic layered double hydroxides are comparatively new materials examined for the adsorption of fluorides and they exhibit good fluoride adsorption capacity. A discussion on various defluoridation methods, adsorbents for defluoridation and recent developments are presented in this chapter.